New insights into the limit for non-partitioning ferrite growth. (March 2015) - Panahi, D.; Van Landeghem, H.; Hutchinson, C.R.; Purdy, G.; Zurob, H.S.
Abstract: The limiting conditions for non-partitioned ferrite growth were investigated under controlled decarburization conditions. An abrupt change in the growth kinetics and morphology of ferrite was observed when the temperature increased above the limit defined by the local equilibrium no-partitioning (LENP) model. The ferrite layer formed below the LENP limit consisted of columnar grains and showed continuous, parabolic growth kinetics. In contrast, ferrite growth above the LENP limit showed two distinct stages. Initially, a thin layer of columnar ferrite grains formed and grew rapidly for a short period of time. In the second stage, the ferrite layer appeared to increase in thickness at a very low rate. The slow growth of the ferrite layer was associated with a strong depletion of carbon content in austenite as well as the formation of new ferrite grains as opposed to the growth of existing grains. The evolution of the carbon concentration in austenite was used to infer the operating interfacial contact conditions as a function of time. The evolution of the interfacial austenite conditions is suggested to penetrate deep into the two-phase region as predicted by ferrite growth theories that account for free-energy dissipation during the austenite-to-ferrite phase transformation.